2023
DOI: 10.33899/ijvs.2022.135489.2482
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of parasitic infections among slaughtered animals in mechanical abattoir

Abstract: Gastrointestinal parasites, such as helminths and protozoa, are abundant parasitic agents of livestock, particularly ruminants. The current study aims to determine the prevalence rate of parasitic infections in large ruminate animals slaughtered in the mechanical abattoir in Alexandria governorate, Egypt. The prevalence was identified through the records of parasitic infections detected in the fecal matter of large ruminate animals in addition to the recorded postmortem examination findings. Three hundred sixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Conversely, Abbas et al [35] and Tiele et al [25] reported a higher prevalence in males. A study by Felefel et al [36] indicated higher infections in females (39.1%) than males (35%), though the difference was statistically insignificant. There may be variations in susceptibility to GI parasitic infections based on gender due to genetic predisposition and fluctuating susceptibility brought on by hormonal regulation [37].…”
Section: Discussionmentioning
confidence: 89%
“…Conversely, Abbas et al [35] and Tiele et al [25] reported a higher prevalence in males. A study by Felefel et al [36] indicated higher infections in females (39.1%) than males (35%), though the difference was statistically insignificant. There may be variations in susceptibility to GI parasitic infections based on gender due to genetic predisposition and fluctuating susceptibility brought on by hormonal regulation [37].…”
Section: Discussionmentioning
confidence: 89%
“…Subsequently, the slide was inspected under 10 × magni cations for the nal assessment and existence of helminthic eggs using an Olympus optical microscope. [43] McMaster egg counting technique A mixture of 1 gram of fecal matter from each sample and 28 ml of saturated salt solution was sieved in another clean container. McMaster counting chambers were lled using a Pasteur pipette with the previous mixture.…”
Section: Microscopic Investigationmentioning
confidence: 99%